The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1099/00221287-148-9-2783
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the xylose-transporting properties of yeast hexose transporters and their influence on xylose utilization

Abstract: For an economically feasible production of ethanol from plant biomass by microbial cells, the fermentation of xylose is important. As xylose uptake might be a limiting step for xylose fermentation by recombinant xyloseutilizing Saccharomyces cerevisiae cells a study of xylose uptake was performed. After deletion of all of the 18 hexose-transporter genes, the ability of the cells to take up and to grow on xylose was lost. Reintroduction of individual hexose-transporter genes in this strain revealed that at inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
233
0
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(256 citation statements)
references
References 30 publications
9
233
0
11
Order By: Relevance
“…The most striking observation amongst the genes with a changed transcript level was the representation of various members of the hexose transport family, including HXT1, HXT2 and HXT4. Interestingly, HXT1 and HXT4 have been associated with d-xylose transport in previous studies [27,62]. To investigate whether the improved fermentation characteristics were indeed due to changes in sugar transport, zero trans-influx assays were performed using both the strain that was only metabolically engineered and the subsequently evolved strain [44].…”
Section: Evolutionary Engineering Of D-xylose-consuming S Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation
“…The most striking observation amongst the genes with a changed transcript level was the representation of various members of the hexose transport family, including HXT1, HXT2 and HXT4. Interestingly, HXT1 and HXT4 have been associated with d-xylose transport in previous studies [27,62]. To investigate whether the improved fermentation characteristics were indeed due to changes in sugar transport, zero trans-influx assays were performed using both the strain that was only metabolically engineered and the subsequently evolved strain [44].…”
Section: Evolutionary Engineering Of D-xylose-consuming S Cerevisiaementioning
confidence: 99%
“…Despite the inherent redox constraints of S. cerevisiae strains based on the xylose reductase/xylitol dehydrogenase strategy, this strategy has resulted in many important insights into the kinetics of d-xylose metabolism by engineered S. cerevisiae strains. These findings include the benefits of overexpression of xylulokinase [29,56], the side role of the S. cerevisiae aldose reductase (Gre3) (besides the heterologous dual specificity xylose reductases) in xylitol formation [66], the role of the enzymes of the non-oxidative part of the pentose phosphate pathway [34,43], characterisation of d-xylose transport [27,62] and many studies on the inhibitor tolerance/sensitivity of d-xylose-consuming strains [54]. The latter will be especially crucial for successful application of d-xylose-consuming S. cerevisiae strains for ethanol production from lignocellulosic hydrolysates (see Sect.…”
Section: Introduction Of Heterologous Genes Encoding Xylose Reductasementioning
confidence: 99%
“…However, inefficiencies due to a redox imbalance between NAD and NADP proton shuttles result in slow pentose metabolism (Bruinenberg et al, 1983). Furthermore, xylose is transported into recombinant S. cerevisiae cells by the same family of hexose transporters (Hxts) that are used for glucose uptake (Hamacher et al, 2002). Because these transporters have over a magnitude greater affinity for glucose than xylose, these recombinant yeast utilize xylose only after depletion of glucose in a pattern of diauxic growth (Kuyper et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the non-oxidative pentose phosphate pathway enhanced xylulose but not xylose fermentation rate in recombinant S. cerevisiae (Johansson and HahnHägerdal, 2002), suggesting limitations prior to xylulose. The Hxt4p, Hxt5p, Hxt7p and Gal2p have been shown to transport xylose, but overexpression of the individual transporter-encoding genes did not enhance the specific growth rate on xylose in recombinant S. cerevisiae (Hamacher et al, 2002). It has also been shown that transport only limits xylose consumption rate at low xylose concentrations (Gardonyi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%